2011
DOI: 10.1016/j.meegid.2010.10.010
|View full text |Cite
|
Sign up to set email alerts
|

Full genomic analysis of a simian SA11-like G3P[2] rotavirus strain isolated from an asymptomatic infant: Identification of novel VP1, VP6 and NSP4 genotypes

Abstract: We report here the full genomic analysis of a simian SA11-like G3P[2] group A rotavirus (GAR) strain, B10, isolated from an asymptomatic infant in Kenya in 1987. By nucleotide sequence identities and phylogenetic analyses, the VP7-VP4-VP2-VP3-NSP1-NSP2-NSP3-NSP5 genes of strain B10 exhibited maximum genetic relatedness to those of the different isolates of simian strain SA11, and were assigned to the G3-P[2]-C5-M5-A5-N5-T5-H5 genotypes, respectively. On the other hand, the VP1, VP6 and NSP4 genes of strain B10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 36 publications
0
18
0
Order By: Relevance
“…The predominant NSP4 genotype E1 identified in the studied area is commonly reported; some studies identified the E2 genotype as the second common genotype [38,39,40,41]. Furthermore, others reported non-common NSP4 genotypes E3, E5, E6 and E13 in human rotavirus strains in Thailand, Brazil, Bangladesh and Kenya [42,43,44,45,46]. …”
Section: Resultsmentioning
confidence: 95%
“…The predominant NSP4 genotype E1 identified in the studied area is commonly reported; some studies identified the E2 genotype as the second common genotype [38,39,40,41]. Furthermore, others reported non-common NSP4 genotypes E3, E5, E6 and E13 in human rotavirus strains in Thailand, Brazil, Bangladesh and Kenya [42,43,44,45,46]. …”
Section: Resultsmentioning
confidence: 95%
“…The new genotypes were found in RVs identified in a variety of host species including humans, cows, pigs, horses, mice, chickens, turkeys, pheasants, South American camelids, and bats. Several of these new genotypes have been published (1, 18, 23, 30, 42, 55, 56, 81, 83, 86, 90). For several other strains, such as RVA/Human-tc/ITA/260-97/1997/G3P[3] (HQ661112-HQ661122), RVA/Cow-tc/JPN/Dai-10/2007/G24P[33] (AB513836-AB513837 and AB573070-AB573078), RVA/Mouse-tc/USA/ETD_822/XXXX/G16P[16] (GQ479947-GQ479957), RVA/Pig-wt/JPN/FGP51/2009/G4P[34] (AB571046-AB571047), and RVA/Pig-wt/JPN/TJ4-1/2010/G26P[unknown] (AB605258), at present only the GenBank accession numbers are available.…”
Section: Update From the Rcwgmentioning
confidence: 99%
“…For example, a Hungarian G6P[14] strain detected in a child with severe diarrhea was found to carry buffalo-, feline-and bovine-like genes in its genomic constellation [106]. A historic Kenyan rotavirus strain detected in an asymptomatic child was found to carry genes of probable simian rotavirus origin and a number of genes whose host species origin could not be elucidated in the absence of sequence information from putative animal hosts [107]. The individual genes of another strain from India showed genetic relatedness with feline, simian and caprine rotavirus strains [108].…”
Section: Evidence and Mechanisms Of Rotavirus Zoonosismentioning
confidence: 99%